FIXED POINT THEOREM FOR MULTIVALUED NON-SELF MAPPINGS SATISFYING JS-CONTRACTION WITH AN APPLICATION - David Aron; Santosh Kumar (Ural Mathematical Journal)
In this paper, we present some fixed point results for multivalued non-self mappings. We generalize the fixed point theorem due to Altun and Minak [2] by using Jleli and Sameti [9] \(ϑ\)-contraction. To validate the results proved here, we provide an appropriate application of our main result.